STRATEGI PENGEMBANGAN USAHA GULA AREN DI DESA RAMBAH TENGAH BARAT KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Fitriana, Laily; Bahar, Edward (E-Journal Sungkai, 2012)
Aren agro industry is a form of industry which use Nira Water as the raw material to beprocessed become sugar and ready to consume and sell in the market. Aren is able to use as agroindustry material, such as Nira Water as raw material in producing Aren Sugar, Vinegar, and Tuak.In this research the writer take one product, that is development of Aren Sugar businesswhich material is Nira Water.The purpose of the research are: 1) to know production aspect,processing aspect, technology aspect, marketing aspect, and organization aspect on agro industrybusiness of Aren Sugar in Rambah Tengah Barat Village Rambah Sub district Rokan HuluRegency.To maximize the income from processing Aren Sugar, so it needs business analysis,because through it, we know how much the income from the Aren Sugar business per month. Thecosts that spent in one month (lost/profit) are; a) Constant cost is Rp 13.225,- b) Variable cost Rp37.495.775,- with R/C ratio 3,27. From the analysis, it was decided that Aren Sugar businessproper to develop.